Human resources : fiftieth anniversary colloquium VI - National Bureau of Economic Research; Schultz, Theodore W. (New York : National Bureau of Economic Research; distributed by Columbia University Press, 1972)
This volume of the fiftieth anniversary series contains the proceedings of the Human Resources Colloquium, which was held on the campus of Clark College, Atlanta University, Atlanta, Georgia on 13 May, 1971
Includes index
kjo 17/01/2019
Loans
Keywords: Human capital; Human resource